Analysis of Mathematics Literacy Ability - Anis Syafiqah Sohaimi; Rahma Dyah Sari Purba; Dwi Maulida Sari; Rahmat Badawi (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2022)
Education can develop students' potential, while mathematics education is an effort to improve students' mathematical abilities and increase students' intelligence. Mathematics is used as a tool to develop these mathematical abilities, this shows that mathematics is a very important science, but many students view mathematics as the most difficult field of study, this is because students often have difficulty understanding math problems so they often do mistakes in solving the given questions. Mathematical Literacy Ability is an ability that supports the development of the five mathematical abilities termed as mathematical power. Therefore, mathematical literacy is referred to as the minimum ability that someone has in the field of mathematics. The type of research used is qualitative research with a descriptive approach. Based on the results of the acquisition of the score for each student given, the score of the results of the mathematical literacy ability test in solving PISA questions for students is in the less category as many as 25 people, 5 is enough and not in the Good category. The overall average is 58.5. It can be seen that the average score of the results of the mathematical literacy ability test is in the Less category.